Research on the development and business trend of holographic technology under 6G network - Wenjun HOU; Bing BAI; Benzhi YANG (Dianxin kexue)
Research on 6G has been carried out on a global scale.Focusing on holographic interactive services under 6G, the requirements for future network performance by studying holographic interactive scenarios and services were analyzed.A basis for business requirements for the design and research and technological evolution of 6G networks was provided.The holographic technology and application status, holographic communication and holographic interaction scenarios, as well as the technical indicators and network performance requirements of the scene business were studied.The holographic technology development stage, development maturity, holographic industry chain under 5G, and holographic technology application field distribution were defined.A holographic scene pool and scene characteristics were constructed, and six types of application scenes were formed based on the characteristics.Through the calculation of technical indicators, the bandwidth performance requirements of holographic portrait transmission were proposed.